Novel pencil-beam scanning proton lattice radiation therapy for the treatment of bulky liver cancer: dosimetric comparison with VMAT-lattice radiotherapy - Li, Yuting; Martin-Paulpeter, Rachael M.; Chung, Christine V.; Aguilar, Miguel A.; Matias, Carlos A.; Delgado, Adrian; Nair, Saurabh S.; Court, Laurence E.; Perles, Luis; Sahoo, Narayan; Zhu, Ronald X.; Poenisch, Falk; et al. (Frontiers in Oncology, 2026)
BackgroundSpatially fractionated radiotherapy (SFRT) delivered as lattice radiotherapy (LRT) creates high-dose ‘vertex’ subvolumes (VTVH) embedded within low-dose ‘valley’ regions (VTVL) to intensify intratumoral dose while minimizing radiation dose and toxicity to organs at risk (OARs). We developed a pencil-beam scanning (PBS) intensity modulated proton therapy (IMPT) LRT planning approach and dosimetrically compared it directly with contemporary photon-based volume modulated arc therapy (VMAT) LRT for liver cancer with bulky tumors.MethodsTwenty-one retrospective liver cases were replanned in RayStation to a single fraction of 20 Gy to VTVH with explicit VTVL sparing (mean dose <5Gy). Primary dosimetric endpoints were VTVH D80 and VTVL mean dose (analogous to mean valley dose), with secondary endpoints of VTVH/VTVL ratios (PVDR-like metrics at D80/D90/D100), VTVL D5/D80, GTV D10/D90, and planning risk volume (PRV) 0.03 cm³ hotspots. Statistical analysis consisted of paired tests (t-test or Wilcoxon signed-rank) after assessing data normality (Shapiro-Wilk tests) and using α=0.05 for significance.ResultsCompared with photon VMAT-LRT, IMPT-LRT significantly reduced VTVL mean dose (p<0.00001) and increased VTVH D80 (p<0.00001), yielding higher VTVH/VTVL ratios at D80/D90/D100 (all p<0.00001). Gross tumor volume (GTV) heterogeneity (D20/D80) significantly increased with proton-LRT (p<0.00001) and OAR hot-spot metrics (PRV D0.03cc) were comparable between both modalities (p=0.71).ConclusionsA robust PBS proton-LRT planning approach was developed and compared to photon VMAT-LRT for large liver tumors. Our IMPT-LRT approach maximizes peak-to-valley separation and simultaneously maintains target coverage while significantly reducing valley dose, as compared to traditional VMAT-LRT. These findings support future prospective clinical evaluation.